A polyoxometalate composite variable color gel with super-long cycle stability, a preparation method thereof and application thereof in an integrated electrochromic device
By combining polyoxometalates, inorganic gels, and organic gels, along with redox species and structural stabilizing agents, the leakage and shedding problems of traditional electrochromic devices have been solved, achieving ultra-long cycle stability and uniform coloring, and simplifying the preparation process.
Patent Information
- Application Number
- CN202511108418.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-08-08
AI Technical Summary
Traditional electrochromic devices suffer from leakage and shedding issues with their polyoxometalate films, resulting in poor cycle stability and complex fabrication processes.
An ultra-long cycle-stable gel is prepared by combining polyoxometalates, inorganic gels (such as magnesium aluminum silicate or lithium magnesium silicate), organic gels (such as hydroxyethyl cellulose), and redox species (such as lithium iodide) in specific proportions and with additives (such as lithium bis(trifluoromethanesulfonylimide) propylene carbonate solution). Combined with a unique cascade structure and hydrophobic film, the device's coloring ability and conductivity are enhanced.
This study achieved ultra-long cycle stability and uniform coloring of electrochromic devices, simplified the fabrication process, and reduced costs.
Smart Images

Figure CN120624000B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of electrochromic devices, and particularly relates to a multi-polyoxometalate composite color-changing gel with super-long cycle stability, a preparation method thereof and application thereof in an integrated electrochromic device. BACKGROUND
[0002] Traditional electrochromic devices are mostly five-layer sandwich structures, namely transparent conductive electrode 1, electrochromic layer, electrolyte layer, ion storage layer and transparent conductive electrode 2, and the structure is very complex and the preparation process is tedious. Multi-polyoxometalate can undergo oxidation and reduction to produce color change due to its unique electron-accepting property, and is widely used in the field of electrochromism. Multi-polyoxometalate is usually processed into a thin film by low-cost electrodeposition or spin coating method, and liquid electrolyte is mostly used, so there is a risk of liquid leakage. Multi-polyoxometalate thin film also has the problem of falling off in traditional electrochromic devices, resulting in poor cycle stability. Magnesium lithium silicate and magnesium aluminum silicate inorganic gel has a unique card palace type lamellar structure and a unique cation accelerated channel, and has high viscosity and high transparency after water absorption and expansion. Hydroxyethyl cellulose is a common gel water retaining agent in the chemical field, which can form a unique hydrophobic film after dissolving water to prevent water loss due to evaporation. It is expected to combine the properties of the three to prepare a multi-polyoxometalate composite color-changing gel with super-long cycle stability. SUMMARY
[0003] The purpose of the present application is to provide a multi-polyoxometalate composite color-changing gel with super-long cycle stability, a preparation method thereof and application thereof in an integrated electrochromic device, which has good electrochromic performance and super-long cycle stability.
[0004] The technical solution adopted by the present application is:
[0005] A multi-polyoxometalate composite color-changing gel with super-long cycle stability, which is composed of multi-polyoxometalate, inorganic gel, organic gel, redox species and structure stabilizing aid; the multi-polyoxometalate is PW 12 or P2W 18 , the inorganic gel is magnesium aluminum silicate gel or magnesium lithium silicate gel, the organic gel is hydroxyethyl cellulose gel, and the redox species is lithium iodide.
[0006] Further, the mass ratio of the multi-polyoxometalate and the redox species in the above-mentioned multi-polyoxometalate composite color-changing gel with super-long cycle stability is 5:4.
[0007] Further, the mass ratio of the inorganic gel and the organic gel in the above-mentioned multi-polyoxometalate composite color-changing gel with super-long cycle stability is 1:1 or 2:1.
[0008] Furthermore, in the aforementioned polyoxometalate composite color-changing gel with ultra-long cycle stability, the structural stabilizing agent is a solution of bis(trifluoromethanesulfonylimide) propylene carbonate.
[0009] A method for preparing a polyoxometalate composite color-changing gel with ultra-long cycle stability as described in any one of the above methods includes the following steps:
[0010] 1) Preparation of inorganic gel: Take inorganic powder, add it to water under rapid stirring, stir for 20 minutes to form inorganic gel;
[0011] 2) Preparation of organic gel: Take organic powder, add it to water under rapid stirring, heat and stir at 70°C for 1 hour to form organic gel;
[0012] 3) Preparation of polyoxometalate composite color-changing gel: Add the polyoxometalate solution to the inorganic gel prepared in step 1) and stir for 10 min; then add the organic gel prepared in step 2) to the mixture and heat and stir for 10 min; then add the structure stabilizing agent to the mixture and stir for 15 min; then add the redox species solution to the mixture and stir for 2 h to obtain the polyoxometalate composite color-changing gel; then sonicate the polyoxometalate composite color-changing gel for 30 min.
[0013] The application of any of the above-mentioned polyoxometalate composite color-changing gels with ultra-long cycle stability in integrated electrochromic devices.
[0014] Furthermore, the above application is carried out in the following way: a polyoxometalate composite color-changing gel is sandwiched between two transparent conductive substrates to assemble an integrated electrochromic device, and the thickness of the polyoxometalate composite color-changing gel interlayer is 50-100μm.
[0015] The beneficial effects of this invention are as follows:
[0016] 1. This invention utilizes a transparent inorganic gel with a unique cascade-like layered structure combined with polyoxometalates. Because this type of inorganic gel carries a negative charge overall, it exhibits good compatibility with anionic polyoxometalates. Hydroxyethyl cellulose, an organic gel, is used as a water-retaining agent. Under aqueous conditions, it forms a hydrophobic film to prevent water evaporation, solving the problem of poor water retention in inorganic gels and preventing cracking during long-term operation. A suitable redox species, lithium iodide, is employed. Lithium iodide has oxidizing properties and can oxidize polyoxometalates reduced to blue to colorless, enhancing the device's coloring and fading abilities. The structural stabilizing agent, lithium bis(trifluoromethanesulfonyl)imide propylene carbonate solution, reduces the overall viscosity of the gel and improves its conductivity. This results in more uniform coloring of the integrated electrochromic device and achieves ultra-long cycle stability.
[0017] 2. The device of the present invention is simple to prepare, easy to operate, and low in cost. Attached Figure Description
[0018] Figure 1 This is a response time diagram of the integrated electrochromic device in Example 1.
[0019] Figure 2 This is a response time diagram of the integrated electrochromic device in Example 2.
[0020] Figure 3 This is an optical contrast diagram of the integrated electrochromic device in Example 2 after 10,000 cycles at 660nm.
[0021] Figure 4 This is an optical contrast diagram of the integrated electrochromic device in Comparative Example 1 after 10,000 cycles at 660nm.
[0022] Figure 5 The image shows the coloring and fading effect of the integrated electrochromic device in Comparative Example 2. In the image, a is a schematic diagram of the initial electrochromic device, b is a coloring effect of the electrochromic device after applying a -3V voltage, and c is a fading effect of the electrochromic device after applying a 1V voltage. Detailed Implementation
[0023] Example 1: An integrated electrochromic device based on an inorganic magnesium aluminum silicate and an organic hydroxyethyl cellulose composite color-changing gel.
[0024] (I) Preparation method
[0025] 1) Preparation of magnesium aluminum silicate gel: Weigh 0.5g of magnesium aluminum silicate into 5mL of deionized water at a mass ratio of inorganic powder to organic powder of 2:1, stir for 20min to make it uniform, and form an inorganic gel for later use.
[0026] 2) Preparation of hydroxyethyl cellulose gel: Weigh 0.25g of hydroxyethyl cellulose into 5mL of deionized water with an inorganic powder to organic powder mass ratio of 2:1, and heat and stir at 70℃ for 1h to form an organic gel for later use.
[0027] 3) Preparation of polyoxometalate composite color-changing gel: 0.3g of PW 12Dissolve in 1 mL of deionized water, completely dissolved after adding step 1) prepared magnesium aluminum silicate gel, stirring 10 min to make it mixed evenly. Again add step 2) prepared hydroxyethyl cellulose gel, heated stirring 10 min mixed evenly. Again take 0.1 g of lithium bis (trifluoromethanesulfonyl) imide dissolved in 1 mL of propylene carbonate (PC), continue to add to the mixed system, stirring 15 min to make it mixed evenly. Again take 0.24 g of lithium iodide dissolved in 1 mL of deionized water, continue to add to the mixed system, stirring 2 h after ultrasonic 30 min to obtain polyoxometalate composite color-changing gel ready for use.
[0028] 4) Assembly of integrated electrochromic device: cut 1.5*2 cm of adhesive tape frame, take two pieces of clean FTO glass, paste the adhesive tape frame on the conductive surface of one of them, pour the polyoxometalate composite color-changing gel into the adhesive tape frame, take another piece of FTO glass, cover the polyoxometalate composite color-changing gel, press hard to get an integrated electrochromic device, the thickness of the polyoxometalate composite color-changing gel sandwich is controlled at 50-100 μm.
[0029] (B) Performance test
[0030] In the prepared device, -3V voltage is applied for 20 s for coloring, 1V voltage is applied for 30 s for bleaching, tested in ultraviolet spectrophotometer, wavelength is 660 nm, the response time of the device is as shown in Figure 1 The coloring time is 7.3 s and the bleaching time is 7 s.
[0031] Example 2 An integrated electrochromic device based on inorganic lithium magnesium silicate and organic hydroxyethyl cellulose composite color-changing gel
[0032] (A) Preparation method
[0033] 1) Preparation of lithium magnesium silicate gel: according to the mass ratio of inorganic powder to organic powder 1:1, 0.3 g of lithium magnesium silicate is weighed and dissolved in 5 mL of deionized water under rapid stirring, stirring for 20 min to make it uniform, forming an inorganic gel for standby.
[0034] 2) Preparation of hydroxyethyl cellulose gel: according to the mass ratio of inorganic powder to organic powder 1:1, 0.3 g of hydroxyethyl cellulose is weighed and dissolved in 5 mL of deionized water under rapid stirring, heated and stirred at 70℃ for 1 h to form an organic gel for standby.
[0035] 3) Preparation of polyoxometalate composite color-changing gel: 0.3 g of P2W 18Dissolve in 5 mL of deionized water, completely dissolved after adding step 1) prepared by magnesium lithium silicate gel, stirring 10 min to make it mixed evenly. Again add step 2) prepared by hydroxyethyl cellulose gel, heated stirring 10 min mixed evenly. Again take 0.1 g of lithium bis (trifluoromethanesulfonyl) imide dissolved in 5 mL of propylene carbonate (PC), continue to add to the mixed system, stirring 15 min to make it mixed evenly. Again take 0.24 g of lithium iodide dissolved in 1 mL of deionized water, continue to add to the mixed system, stirring 2 h after ultrasonic 30 min to get polyoxometalate composite color-changing gel ready for use.
[0036] 4) Assembly of integrated electrochromic device: cut 1.5*2 cm of adhesive tape frame, take two pieces of clean FTO glass, paste the adhesive tape frame on the conductive surface of one of them, pour the polyoxometalate composite color-changing gel into the adhesive tape frame, take another piece of FTO glass, cover the polyoxometalate composite color-changing gel, press hard to get an integrated electrochromic device, the thickness of the polyoxometalate composite color-changing gel sandwich is controlled at 50-100 μm.
[0037] (B) Performance test
[0038] In the prepared device, -3V voltage is applied for 20 s to color, 1V voltage is applied for 30 s to fade, tested in ultraviolet spectrophotometer, wavelength is 660 nm, the response time of the device is as shown in Figure 2 , the coloring time is 7 s, and the fading time is 7.6 s.
[0039] In the prepared device, -3V voltage is applied for 10 s to color, 1V voltage is applied for 10 s to fade, tested in ultraviolet spectrophotometer, wavelength is 660 nm, the transmittance change of the device is as shown in Figure 3 , the initial ΔT is 92% under -3~1V voltage, and the transmittance almost does not decrease after 10000 cycles.
[0040] Comparative example 1
[0041] (A) Preparation method
[0042] 1) Preparation of magnesium lithium silicate gel: according to the mass ratio of inorganic powder to organic powder is 1:1, 0.3 g of magnesium lithium silicate is dissolved in 5 mL of deionized water under rapid stirring, stirring 20 min to make it uniform, forming inorganic gel ready for use.
[0043] 2) Preparation of polyoxometalate inorganic color-changing gel: 0.3 g of P2W 18Dissolve 0.3 g of lithium magnesium silicate in 5 mL of deionized water, and stir for 10 min to form a homogeneous inorganic gel. Then, dissolve 0.1 g of lithium bis-trifluoromethanesulfonimide in 5 mL of propylene carbonate (PC), and add the solution to the inorganic gel. Stir for 15 min to form a homogeneous mixture. Then, dissolve 0.24 g of lithium iodide in 1 mL of deionized water, and add the solution to the mixture. Stir for 2 h, and then ultrasonically treat the mixture for 30 min to obtain a polyoxometalate inorganic color-changing gel.
[0044] 3) Assembly of the integrated electrochromic device: cut a 1.5*2 cm adhesive tape frame, and place the frame on the conductive surface of one of the two cleaned FTO glasses. Pour the polyoxometalate inorganic color-changing gel into the adhesive tape frame, and place the other FTO glass on the polyoxometalate inorganic color-changing gel. Press the two glasses to obtain an integrated electrochromic device, and control the thickness of the polyoxometalate inorganic color-changing gel to be 50-100 μm.
[0045] (B) Performance test
[0046] In the prepared device, coloration was performed by applying a voltage of -3 V for 10 s, and bleaching was performed by applying a voltage of 1 V for 10 s. The transmittance change of the device was tested in a UV spectrophotometer at a wavelength of 660 nm, and the results are shown in Table 1. Figure 4 As shown in Table 1, the initial ΔT was 95% under a voltage of -3-1 V, and the ΔT decreased to 83% after 10,000 cycles.
[0047] Comparative Example 2
[0048] (A) Preparation method
[0049] 1) Preparation of lithium magnesium silicate gel: according to a mass ratio of inorganic powder to organic powder of 1:1, 0.3 g of lithium magnesium silicate was dissolved in 5 mL of deionized water under rapid stirring, and stirred for 20 min to form a homogeneous inorganic gel.
[0050] 2) Preparation of hydroxyethyl cellulose gel: according to a mass ratio of inorganic powder to organic powder of 1:1, 0.3 g of hydroxyethyl cellulose was dissolved in 5 mL of deionized water under rapid stirring, and heated and stirred at 70°C for 1 h to form a homogeneous organic gel.
[0051] 3) Preparation of polyoxometalate color-changing gel: 0.3 g of P2W 18Dissolve in 5 mL of deionized water, completely dissolved after adding step 1) prepared magnesium lithium silicate gel, stirring 10 min to make it mixed evenly. Then add the hydroxyethyl cellulose gel prepared in step 2), heated and stirred for 10 min to mix evenly. Then take 0.1 g of lithium bis-trifluoromethanesulfonimide dissolved in 5 mL of propylene carbonate (PC), continue to add to the mixed system, stir for 15 min to make it mixed evenly. Then ultrasonic for 30 min to get polyoxometalate color-changing gel ready for use.
[0052] 4) Assembly of integrated electrochromic device: cut 1.5*2 cm of adhesive tape frame, take two pieces of clean FTO glass, paste the adhesive tape frame on the conductive surface of one of them, pour the polyoxometalate color-changing gel into the adhesive tape frame, take the other FTO glass, cover the polyoxometalate color-changing gel, press hard to get an integrated electrochromic device, the thickness of the polyoxometalate color-changing gel sandwich is controlled at 50-100 μm.
[0053] (B) Performance test
[0054] In the prepared device, -3V voltage is applied for 10s for coloring, 1V voltage is applied for 10s for bleaching, the real device diagram is as shown in Figure 5 The device can color at -3v, but the bleaching is not complete at 1V voltage.
[0055] PW used in the example 12 It is an analytical reagent phosphotungstic acid hydrate (CAS number: 12501-23-4) purchased directly, without further purification treatment, and used directly.
[0056] P2W used in the example and comparative example 18 The synthesis method is as follows:
[0057] Dissolve Na2WO4·2H2O (analytical pure, 260 g; 0.79 mol) sample in 300 mL of deionized water at room temperature, and slowly add 200 mL of 4 mol / L HCl aqueous solution to the Na2WO4 aqueous solution and stir evenly, after the mixture changes from turbid to clear, add 200 mL of 4M H3PO4 aqueous solution. The light yellow solution obtained is refluxed at 150℃ for 24 hours, after the reflux is completed, the solution is cooled to room temperature, then 150g KCl is added, the obtained precipitate is the target product, after filtration and drying, P2W 18 crude product is obtained. Dissolve P2W 18 crude product in 500 mL of boiling deionized water, filter out the insoluble impurities while hot, the filtrate is placed in a 500 mL beaker and cooled to room temperature, then put it in the refrigerator at 4℃, after 24 hours, pure P2W 18 yellow crystals can be obtained by filtration.18 P2W used in the present application was obtained after drying at room temperature 18 (yield 147 g).
Claims
1. A polyoxometalate complex discolored gel having super-long cyclic stability, characterized in that, The multi-metal oxyanion complex discoloring gel is composed of multi-metal oxyanion, inorganic gel, organic gel, redox species and structure stabilizing assistant; the multi-metal oxyanion is PW 12 or P2W 18 , the inorganic gel is magnesium aluminum silicate gel or magnesium lithium silicate gel, the organic gel is hydroxyethyl cellulose gel, the redox species is lithium iodide, and the structure stabilizing assistant is lithium bis-trifluoromethanesulfonylimide propylene carbonate solution.
2. The polyoxometalate composite metameric gels with ultra-long cyclic stability according to claim 1, characterized in that, The mass ratio of the polyoxometalate and the redox species is 5:
4.
3. The polyoxometalate composite metameric gels with ultra-long cyclability according to claim 1, characterized in that, The mass ratio of the inorganic gel and the organic gel is 1:1 or 2:
1.
4. A process for the preparation of a polyoxometalate complex multichromic gel with super-long cyclic stability according to any one of claims 1 to 3, characterized in that, The method comprises the following steps: 1) Preparation of the inorganic gel: take the inorganic powder and add it into water under rapid stirring, stir for 20 min to form the inorganic gel; 2) Preparation of the organic gel: take the organic powder and add it into water under rapid stirring, heat and stir at 70 ℃ for 1 h to form the organic gel; 3) Preparation of the polyoxometalate composite color-changing gel: add the polyoxometalate solution into the inorganic gel prepared in step 1), stir for 10 min; then add the organic gel prepared in step 2) into the mixed system, heat and stir for 10 min; then continue to add the structure stabilizing aid into the mixed system, stir for 15 min; then continue to add the redox species solution into the mixed system, stir for 2 h to obtain the polyoxometalate composite color-changing gel; then ultrasonically treat the polyoxometalate composite color-changing gel for 30 min.
5. Use of a polyoxometalate complexing multichromic gel with super-long cyclability according to any one of claims 1 to 3 in an all-in-one electrochromic device, characterized in that, The method is as follows: sandwich the polyoxometalate composite color-changing gel between two transparent conductive substrates to assemble an integrated electrochromic device, and the thickness of the polyoxometalate composite color-changing gel sandwich is 50-100 μm.
Citation Information
Patent Citations
Electrochromic gel, preparation method and application thereof and multicolor electrochromic display
CN117965158A
Interface enhanced gel-based electrochromic device and preparation method thereof
CN120178566A